IMPLEMENTASI PENDEKATAN PEMBELAJARAN BERBASIS STUDENT CENTERED LEARNING - Febrian Alwan Bahrudin (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2019)
This research is about the Learning Implementation using The ‘Student Centered Learning’ Base in the Pancasila and Citizenship Education Department, the learning process activity can be divided into two types of approaches, such as the learning approach with ‘Teacher Centered Learning’ (TCL) base, and with the ‘Student Centered Learning’ (SCL) base. The approach of learning using the ‘Teacher Centered Learning’(TCL) base is an activity in which the lecturer becomes the main subject in the process of learning, and within the learning process using the ‘Teacher Centered Learning’ (TCL) the lecturer will be a lot more active than the students and thus have a much more important role in this method when it comes to giving the materials for learning. In the ‘Teacher Centered Learning’ (TCL) base method, students tend to be much less active in the learning process, whereas the ‘Student Centered Learning’ (SCL) is a method that gives the students the chance to be active in the process, or in this case, the students are now the main subject of the learning process. The approach of this research is based on qualitative approach and also using descriptive study method. The implementation of learning using the ‘Student Centered Learning’ (SCL) is done through several stages, beginning with planning, execution, and ends with evaluation. In the planning stage the lecturer prepares the administrative part of learning, in which includes making lesson plan, and preparing things that support the learning process, such as media, learning resources, or other innovations that supports learning. This stage of the learning process aims to determine the initial steps so that the learning process can run effectively and efficiently, the making of the lesson plan which positions the students to have a much more dominant role than lecturers is a form of learning using the ‘Student Centered Learning’ (SCL) method, in this stage the implementation of learning makes the students take more part in the learning process compared to lecturers, students are required to be active and creative in the learning process, in this activity the use of learning media is very helpful to be able to implement student centered learning. Student's active role can be applied through class presentations about the material being discussed, besides that the use of electronic-based learning or e-learning has been applied in the Department of Pancasila and Citizenship Education. The last stage is the closing stage where the usual thing to do is to reflect on the learning that has been done with the intent to evaluate so students and lecturers can determine learning improvements at the next meeting.